A lce Rig ston rgyal moʼi rnam thar and Las can bu mo Me tog gsal sgron maʼi rnam thar : two texts of the rnam thar genre from the Padma-bkod area of Tibet (Trayang and Jamyang Samten, 1977)
Two Tibetan stories for dramatization.